Activity-Based Costing (ABC) in the Manufacturing Industry: A Literature Review - Saeed, Abdulmalek Marwan M.; Widyaningsih, Aristanti; Khaled, Amgad S. D. (Journal of Developing Economies, 2023)
Activity-based costing (ABC) is a way to figure out actual costs. It has become an essential part of both manufacturing and service organizations. This study aims to figure out the effect of the ABC on the manufacturing system. The data was collected from different countries. The method of this study is the systematic Literature Review of the last ten years, 2012-2022. Activities-based costing (ABC) is a good system because it was adopted by many manufacturing businesses to achieve several benefits, including cost ascertainment, which helped them make wise price decisions, cost reduction, which increased profitability, increased productivity, time and resource savings, and improved production quality. Lack of information and inadequate understanding of how to use the ABC system in their company were to blame for companies that did not accelerate its use. Using activity-based costing is effective.